Structured Copper Mesh for Efficient Oil-Water Separation Processed by Picosecond Laser Combined With Chemical Treatment or Thermal Oxidation - Liang, Zihang; He, Wanying; Chu, Dongkai; Qu, Shuoshuo; Yao, Peng (Frontiers in Nanotechnology, 2021)
Oil-water separation has great practical significance, and can be used to help cope with growing oily industrial sewage discharge or marine oil spills, avoiding water pollution. Smart artificial super-wettable materials used for oil-water separation have aroused enormous interest because of their advantages of energy efficiency and applicability across a wide range of industrial processes. Herein, we report a highly efficient, simple method for oil-water separation using copper mesh fabricated by picosecond laser processing combined with chemical treatment or thermal oxidation. After laser processing, the surfaces of copper mesh show superhydrophilicity (hydrophilicity) and underwater superoleophobicity, which can be used to separate water from oil. While, for the samples after laser and chemical treatment or laser treatment combined with thermal oxidation, the surfaces become superhydrophobic (hydrophobic) and underwater superoleophilic, which can separate oil from water. Moreover, these three kinds of super-wettability meshes show high separation efficiency, achieving more than 99% seperation. Furthermore, the as-prepared mesh can be used for various oil-water mixture separation, such as edible oil, kerosene, diesel, and so on. Thus, this work will provide insights for controllable oil-water separation, and will also be beneficial to the study of microfluidic devices, and smart filters.